Emotional regulation and body dissatisfaction: the mediating role of anger in young adult women - Momeñe, Janire; Estévez, Ana; Herrero, Marta; Griffiths, Mark D.; Olave, Leticia; Iruarrizaga, Itziar (Frontiers in Psychiatry, 2023)
Data availability: All data generated or analyzed during the present study are included in this published article. Reviewers can access the database on request [doi: 10.6084/m9.figshare.19947782]. Ethical Statement: The study followed the ethical principles of the Declaration of Helsinki (2013) and ethical approval for the study was provided by the Deontological Commission of the Faculty of Psychology of the Complutense University of Madrid (with reference Ref. 2020/21-035).Informed Consent and consent to publish: Informed consent was obtained from all individual participants included in the study.